Efektivitas BIMTEK di Masa Pandemi Bagi Petani Milenial di Kabupaten Soppeng dan Kabupaten Wajo Provinsi Sulawesi Selatan - Rahman, Luthfi Abdur; Sugihardjo, Sugihardjo; Suminah, Suminah; Hanifah, Vyta Wahyu (Universitas Muhammadiyah Semarang, 2024)
Realising the commitment to develop the agricultural sector requires quality human resources. The millennial generation is the right target for the realisation of transformations that will change the way farmers undergo agricultural business management both in terms of quality and quantity In the perspective of accelerating the dissemination of technological innovation, it is necessary to carry out mentoring activities for the millennial farmer movement. One of the assistance is done through the implementation of technical guidance. This study aims to determine the effectiveness of the technical guidance method in increasing farmers' knowledge in Soppeng Regency and Wajo Regency by looking at differences in pre-test and post-test scores through the Wilcoxon test and seeing the relationship between participant characteristics and the results of pre-test and post-test scores. The results of the study showed that the technical guidance method had an effect on improving farmers' knowledge as seen from the difference in pre-test and post-test scores. The increase in the results of the pre-test post-test value is inseparable from the relationship between the personal characteristics of the participants, although with a weak leve